Hamka's Thoughts on Educators in Islamic Education - Jias Mengki; Syamsul Rijal; Silahuddin Silahuddin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study is backgrounded by various problems that arise in education due to the decadence of community morals, most of which are carried out by the younger generation, whose most still hold the title of students are still bound in formal educational institutions. The imbalance between intellectual input and character building gives rise to attitudes from the community towards the ability of educators as educational agents who are responsible for meeting the needs of students, both spiritual, intellectual, moral, and physical needs of students by pursuing the development of their potential, which includes affective, cognitive, and psychomotor potential by the values of Islamic teachings. This attitude shows the low awareness of the importance of integrating the roles of parents, teachers, and the community as educators, each occupying a vital position in forming complete students regarding intellectual, moral, and righteousness to Allah SWT. This study aims to find out 1) Hamka's thoughts about educators in Islamic education, 2) the Characteristics of educators in Islamic education according to Hamka, and 3) The relevance of Hamka's thoughts about educators in Islamic education. Based on the data collected in the form of descriptions, this research uses a figure study or historical approach where the researcher examines a character's thoughts, be they problems, situations, or conditions that affect his thinking.